Exploring the Trophic Spectrum: Placing Mixoplankton Into Marine Protist Communities of the Southern North Sea - Schneider, Lisa K.; Flynn, Kevin J.; Herman, Peter M. J.; Troost, Tineke A.; Stolte, Willem (Frontiers in Marine Science, 2020)
While traditional microplankton community assessments focus primarily on phytoplankton and protozooplankton, the last decade has witnessed a growing recognition of photo-phago mixotrophy (performed by mixoplankton) as an important nutritional route among plankton. However, the trophic classification of plankton and subsequent analysis of the trophic composition of plankton communities is often subjected to the historical dichotomy. We circumvented this historical dichotomy by employing a 24 year-long time series on abiotic and protist data to explore the trophic composition of protist communities in the Southern North Sea. In total, we studied three different classifications. Classification A employed our current knowledge by labeling only taxa documented to be mixoplankton as such. In a first trophic proposal (classification B), documented mixoplankton and all phototrophic taxa (except for diatoms, cyanobacteria and colonial Phaeocystis) were classified as mixoplankton. In a second trophic proposal (classification C), documented mixoplankton as well as motile, phototrophic taxa associated in a principle component analysis with documented mixoplankton were classified as mixoplankton. In all three classifications, mixoplankton occurred most in the inorganic nutrient-depleted, seasonally stratified environments. While classification A was still subjected to the traditional dichotomy and underestimated the amount of mixoplankton, our results indicate that classification B overestimated the amount of mixoplankton. Classification C combined knowledge gained from the other two classifications and resulted in a plausible trophic composition of the protist community. Using results of classification C, our study provides a list of potential unrecognized mixoplankton in the Southern North Sea. Furthermore, our study suggests that low turbidity and the maturity of an ecosystem, quantified using a newly proposed index of ecosystem maturity (ratio of organic to total nitrogen), provide an indication on the relevance of mixoplankton in marine protist communities.